2022
DOI: 10.1177/0734242x221123495
|View full text |Cite
|
Sign up to set email alerts
|

Rearing performance of black soldier fly (Hermetia illucens) on municipal biowaste in the outdoor ambient weather conditions of Pakistan and Indonesia

Abstract: The availability and continuous supply of black soldier fly larvae (BSFL) is crucial for efficient operation of a BSF biowaste recycling facility. Its rearing performance was for the first time investigated in Pakistan under outdoor ambient weather conditions. Comparison of the findings with the BSF rearing performance of Indonesia’s facility highlights the life stages needing special attention. In Pakistan, mean BSF emergence, hatching and survival rate of 58.8% (SD 15.2), 44.5% (SD 21.8) and 91.4% (SD 1.68) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The experiment spanned until 70% of the larvae had transformed into prepupae, concluding after 22 days post-hatching [12]. The trays containing the larvae were weighed to determine both the final larval weight and the residual weight, which comprised the frass (larval excrement) and any unprocessed waste.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment spanned until 70% of the larvae had transformed into prepupae, concluding after 22 days post-hatching [12]. The trays containing the larvae were weighed to determine both the final larval weight and the residual weight, which comprised the frass (larval excrement) and any unprocessed waste.…”
Section: Methodsmentioning
confidence: 99%
“…The observed adverse effect of air humidity on phosphorus accumulation in our study might be attributed to its potential to limit microbial activity essential for nutrient mineralization and organic matter decomposition. Previous studies [39][40][41] have demonstrated that the optimal air humidity range for BSFL typically falls within 40% to 70%. Thus, deviations from this range can impact the nutrient cycling in the composting system.…”
Section: Phosphorus and Potassium Accumulation In Frass Fertilizer As...mentioning
confidence: 99%
“…They can grow on waste and byproducts; additionally, they have a high feed conversion e ciency and a low risk of transmission of zoonotic infections (Wang et al 2007; Wang et al 2017;Mahmood et al 2021). Among the insect species capable of rapidly producing signi cant biomass under controlled rearing conditions, the black soldier y is currently the main species widely studied for its high capacity for waste degradation and its use as a feed ingredient (Makkar et al, 2014, Mahmood et al 2023. It is a protein source with a well-balanced essential amino acid (EAA) pro le that is almost comparable to that of sh meal (Barroso et al 2014;Muller et al 2017;Chia et al 2020;Adebayo et al 2021).…”
Section: Introductionmentioning
confidence: 99%